A Case of Maxillary Tumour with Difficult Airway - Soubhagya Kumar Das; Jyoshna Mishra; Shree Nanda; Hari Krishna Dalai (Academia Anesthesiologica International, 2016)
A young girl presented with a tumour of the maxilla that had deformed her facial features and dentition and also affected her normal breathing. Preoperative airway assessment indicated not only probability of difficulty in intubating the trachea, but also inability to ventilate through the face mask. In spite of unavailability of sophisticated instruments, the airway could be secured with judicious planning and preparations.